The slaves of the churches a history - Sommar, Mary E. 1953- (New York, NY Oxford University Press, 2020)
This is the story of how the church sought to establish norms for slave ownership on the part of ecclesiastical institutions and personnel and for others' behaviour toward such slaves. The story begins in the New Testament era, when the earliest Christian norms were established, and continues through the late Roman Empire, the Germanic kingdoms, and the Carolingian Empire, to the thirteenth-century establishment of a body of ecclesiastical regulations (canon law) that would persist into the twentieth century. Chronicles, letters, and other documents from each of the various historical periods, along with an analysis of the various policies and statutes, provide insight into the situations of these unfree ecclesiastical dependents.
Also issued in print: 2020. - Includes bibliographical references and index. - Description based on online resource; title from home page (viewed on August 24, 2020)
Keywords: Slavery and the church -- History -- to 1500; Slavery -- Religious aspects -- Christianity; Church History -- Primitive and early church, ca. 30-600; Church History -- Middle Ages, 600-1500